Antimicrobial and immunomodulatory activity of beta-defensin from the Chinese spiny frog (Quasipaa spinosa). (January 2022) - Yu, Shui-Sheng; Zhao, Zeng-Hui; Gong, Xiao-Fei; Fan, Xiao-Li; Lin, Zhi-Hua; Chen, Jie
Abstract: The β-defensins are important components of the vertebrate innate immune system. While mammalian β-defensins have wide-ranging antibacterial and immunomodulatory activities, those of amphibians remain largely uncharacterised. In this study, β-defensin cDNA was identified from the skin transcriptome of the Chinese spiny frog Quasipaa spinosa . This β-defensin (QS-BD) consists of a signal and a mature peptide. Sequence alignments with other amphibian β-defensins showed conservation of the functional mature peptide and that its closest relative is β-defensin from Zhangixalus puerensis . Synthetic QS-BD showed antibacterial activity against Vibrio vulnificus, Vibrio harveyi, Streptococcus iniae, and Aeromonas hydrophila . QS-BD showed bactericidal activity by destroying the cell membrane integrity, but did not hydrolyse genomic DNA. QS-BD treatment promoted respiratory bursts and upregulated the expression of interleukin-1β and tumour necrosis factor-α in the murine leukemic monocyte/macrophage cell line RAW264.7. This is the first demonstration of immunomodulatory activity by an amphibian β-defensin. Highlights: We cloned and characterized the Chinese spiny frog β-defensin (QS-BD). QS-BD synthetic peptide exhibited in vitro antimicrobial activity. QS-BD synthetic peptide showed bactericidal activity by destroying the cell membrane integrity. QS-BD synthetic peptide promoted respiratory bursts and upregulated the expression of IL-1β and TNF-α in RAW264.7.